(untitled) (Praxis Educativa, 2018)
The importance of socioemotional skills development in higher education has been emphasized in several international documents. Among these skills, emotional intelligence (EI) has demonstrated multiple benefits in professionals. However, few studies analyze the challenges involved in its implementation at the university classrooms or systematize tools, through solid theoretical models which root theoretical postulates in practical activities. Therefore, this work has two aims: first, to expose the challenges involved in promoting EI in university classrooms, and second, to provide general tools to promote EI in the classroom through various techniques organized under Mayer and Salovey´s model.